Essential features of teaching Spanish-speaking students aspectual specifics of Russian verbs in Russian as a foreign language classes - A. S. Kalashova; M. K. Gusarenko (Вестник Северо-Кавказского федерального университета, 2023)
The purpose of the article is to present the results of research focused on identifying the difficulties Spanishspeaking students have to face while studying aspectual specifics of Russian verbs in Russian as a foreign language classes, in order to develop a set of effective exercises for classes of Russian grammar. The authors proceeded from the well-known theory that grammar and, in particular, various categories of the verb, are one of the most susceptible to interference and problematic aspects of the language. In this case, the most difficult verb category is its aspect, since representatives of different cultures understand and interpret this category in accordance with the system of their own language and world perception. In the course of the study the authors carried out some experimental work, which included psychological, pedagogical and sociological methods of collecting information (system analysis, questioning, interviewing, observation, conversation, experimental assessments, static processing). The research is based on the method of pedagogical experiment. The study was conducted at the Preparatory Department for foreign students at the North Caucasus Federal University. A detailed analysis of the results of experimental work made it possible to identify typical difficulties Spanish-speaking have to face when studying the aspectual features of verbs of movement in Russian. Taking into account the data obtained, the authors developed a set of exercises for teaching Spanish-speaking students the aspectual specifics of the Russian verbs, which can be used in Russian as a foreign language classes in addition to the tasks offered in different textbooks.